An energy-based model for the wear of unidirectional carbon fiber reinforced epoxy. (December 2020) - Cheng, B; Kortschot, M
The wear resistance of unidirectional carbon fiber reinforced epoxy under severe abrasive sliding conditions was studied. It was found that unidirectional laminates tested with the fibers parallel to the sliding direction (UDp) were more wear resistant than the same laminates tested with fibers transverse to the sliding direction (UDap) under the same set of test conditions. A novel energy-based model was developed to explain the difference in the wear rates. It was found that the difference in wear rates between the two orientations was due to differences in the average volume to surface area ratio of the debris, the energy required to generate new surfaces, and a new k factor that represents the fraction of the total friction energy used for creating wear particles. Furthermore, wear volume per sliding distance was found to be linearly proportional the total frictional energy dissipation for both orientations. These findings can be used to simplify wear predictions for industrial applications.